Relationship between mechanical properties and crystal structure in cocrystals and salt of paracetamol. (2nd January 2017) - Ahmed, Hamzah; Shimpi, Manishkumar R.; Velaga, Sitaram P.
Abstract: Objectives were to study mechanical properties of various solid forms of paracetamol and relate to their crystal structures. Paracetamol form I (PRA), its cocrystals with oxalic acid (PRA-OXA) and 4, 4-bipyridine (PRA-BPY) and hydrochloride salt (PRA-HCL) were selected. Cocrystals and salt were scaled-up using rational crystallization methods. The resulting materials were subjected to different solid-state characterizations. The powders were sieved and 90–360 µm sieve fraction was considered. These powders were examined by scanning electron microscopy (SEM) and densities were determined. Tablets were made at applied pressures of 35–180 MPa under controlled conditions and the tablet height, diameter and hardness were measured. Tensile strength and porosity of the tablets were estimated using well known models. Crystal structures of these systems were visualized and slip planes were identified. Cocrystal and salt of PRA were physically pure. Sieved powders had comparable morphologies and particle size. The apparent and theoretical densities of powders were similar, but no clear trends were observed. The tensile strengths of these compacts were increased with increasing pressure whereas tabletability decreased in the order oxalic acid > PRA-HCL ≈ PRA-OXA > BPY > PRA-BPY. Tablet tensile strength decreases exponentially with increasing porosity with the exception of PRY-BPY and BPY. Slip plane prediction based on attachment energies may not be independently considered. However, it was possible to explain the improved mechanical properties of powders based on the crystal structure. Cocrystallization and salt formation have introduced structural features that are responsible for improved tableting properties of PRA.